Rehabilitation in children and adolescents undergoing stem cell transplantation: A pilot study focused on motor performance. (28th September 2022) - Rossi, Francesca; Zucchetti, Giulia; Esposito, Maria; Berchialla, Paola; Sciannameo, Veronica; Vassallo, Elena; Saglio, Francesco; Chamorro Viña, Carolina; Scarrone, Silvia; Vittorini, Roberta; Fagioli, Franca
Abstract: Objectives: The aim of this pilot trial is evaluating the preliminary effectiveness of two in‐hospital interventions in the maintenance of motor performance in children/adolescents undergoing hematopoietic stem cell transplantation (HSCT). Secondary objectives investigated the interventions' feasibility, impact on fatigue and to what degree the subjects' maintained their ankle dorsiflexion range of movement (ROM), functional mobility, muscle strength and flexibility. Methods: This trial included 5‐ to 18‐year‐old participants, affected by oncological and non‐oncological diseases during hospitalisation for autologous/allogenic HSCT. The subjects were assigned to an exercise group (EG), or a counselling group based on a cluster model based on inpatient timeframe. The EG subjects performed strengthening, stretching and aerobic exercises for 30 min/5 days a week. Both groups followed rehabilitation counselling indications (RCI), 7 days a week. Results: Forty‐nine participants were enrolled (median age = 12.9 years) (EG n  = 36). In both groups the participants maintained their baseline motor performance and ankle ROM, and the children/adolescents and parents reduced their levels of fatigue. However, the interventions were not effective in maintaining strength. Conclusion: In maintaining the subjects' motor performance, the RCI results are significant because they pave the way for the application in clinical practice contexts where there are poor rehabilitation resources. Clinical Trials registration NCT03842735.